(untitled) (Vietnam Journal of Community Medicine, 2026)
Background: Stroke is a leading cause of mortality and long-term disability in adults, in which recovery of walking ability plays a crucial role for patients with lower-limb paralysis. Recently, the GTR-A adaptive robotic gait training system has been implemented at the Rehabilitation Center of Bach Mai Hospital; however, its clinical effectiveness in Vietnam has not been fully evaluated. This study aimed to assess the effectiveness of lower-limb rehabilitation in stroke patients using the GTR-A system. Methods: A prospective, non-controlled interventional study with a pre–post design and a comparative analysis between two intervention groups was conducted on 32 patients with post-stroke hemiplegia and a Functional Ambulation Category (FAC) score ≥2. Patients were randomly assigned to either a Passive training group or an Active-Assisted training group. The robotic gait training program using the GTR-A system was performed three sessions per week for one month. Outcome measures included heart rate parameters, FAC, Berg Balance Scale (BBS), Timed Up and Go test (TUG), and patient satisfaction. Results: After the intervention, both groups showed statistically significant improvements in most outcome measures (p<0.05). The Active-Assisted group demonstrated greater improvement in BBS scores compared with the Passive group. Heart rate values increased after training, reflecting appropriate exercise intensity within a safe physiological range. Patient satisfaction scores increased significantly in both groups (p<0.001). Conclusion: Lower-limb rehabilitation using the GTR-A robotic gait training system significantly improves balance, motor control, and mobility in patients after stroke. Active-assisted training shows certain advantages over passive training.